A judicialização de medicamentos e o sentido corretivo da atuação judicial: Judiciário e a consolidação da política de assistência farmacêutica no Brasil - Tiago Lopes Coelho (2014)
Think the role of the judiciary is one of the great challenges of democratic societies . Identify the limits of judicial activity and the possibilities for control over political activity is a difficult and controversial task. Currently , this task has become even more complex due to targeted judicial proactive in ensuring the effectiveness prestacionais social rights. This "new approach " has broadened the horizons of judicial action , reconfigured the relations between the branches of government and rocked several structures that served as guide in the task of pointing out the limits and possibilities of judicial action . The involvement of the judiciary in the enforcement of social rights prestacionais process is one of the most difficult issues faced by contemporary constitutionalism not only because it confronts , inevitably , with the complex debate on judicial action on unconstitutional omissions and is hit directly by the impact of the absence of adequate social rights dogmatic , but mainly because it 's difficult to think of the distinction between law and politics . Over a considerable period after the enactment of the 1988 Federal Constitution, prevailed in Brazil , the understanding that the judiciary could not participate in the realization of social rights prestacionais process. Today , Brazil's situation is different , and follows the same direction as the international trend . The right to health is the most responsible for seeking judicial intervention to ensure effectiveness prestacionais rights. As a rule, the judiciary is driven by individual demands asking medicines . Judicial involvement in the execution process of this right points to the inadequacy of policy choices . What would be the state with the Legalization of Health is that despite the undeniable progress of SUS , the permanent gap between " legal text and the institutional reality " would result from a failure of policy. The judiciary wins the sense of corrective institution , given its responsibility for achieving the constitutional objectives in this context . However , you can not assume the concealer effectively result of judicial action . In this sense the present work aims to analyze the corrective potential of judicial action on the individual demands for drugs in two ways . On the one hand , the verification of decision levels achieved by the judiciary in this kind of demand. Second, based on the differentiation of activities performed by the judiciary and the political branches as taken .